Innovation of Digital Transformation Platform for Scales Up Leading Sectors Through PADIGO (Pasar Digital Indonesia) Towards Sociopreneurship Based Sustainable Development - Amaliyah, Khoirotul; Sulistyowati, Raya (Journal of Business Management Education (JBME), 2025)
Indonesia is an agrarian and maritime country with significant potential in key sectors such as agriculture, plantations, livestock, and fisheries. The contribution of the agricultural sector reached around 13.28 percent of Gross Domestic Product (GDP) in 2021, making it the second-largest sector after the manufacturing industry. Data from the Central Statistics Agency (BPS) shows that the GDP in the agricultural sector, at prevailing prices (ADHB), reached IDR 2.25 quadrillion throughout 2021. Even during the pandemic, the agricultural sector demonstrated its resilience in facing economic instability and became one of the main drivers of national economic recovery. However, many farmers, local producers, and fishermen still face challenges in reaching broader markets, improving product quality, and obtaining fair profits.The purpose of this study is to analyze how the PADIGO (Pasar Digital Indonesia) application can address the various challenges faced by the agriculture, plantation, livestock, and fisheries sectors in reaching wider markets, improving product quality, and achieving fair profits. Research and Development (RD) methodology is employed in this study, which involves data collection based on relevant variables. The research uses a 4D development approach (define design develop disseminate). Primary and secondary sources are utilized for this analysis. This discussion will outline how the PADIGO application, with its features such as Market, Connect, Payment, Logistic, Event, Real-Time Market, Forum, and Regulation, can address the challenges faced by the agricultural sector and related sectors. By leveraging digital technology, PADIGO is capable of overcoming the various obstacles faced by farmers, local producers, and fishermen, while supporting sustainable, inclusive, and efficient economic growth. Through PADIGO, local producers have broader market access, can improve product quality, and earn fairer profits, thus contributing to community welfare and environmental sustainability.